Genomic epidemiology of Salmonella and Campylobacter in poultry production: Quantifying the contribution of primary breeders - David J. Lipman (Proceedings of the National Academy of Sciences, 2026)
The US broiler production system processes over 9.3 billion chickens annually through a highly integrated pyramid structure where two primary breeding companies supply genetic stock to approximately 40 major integrators operating nationwide. To provide a quantitative, system-wide estimate of contamination origins, I analyzed whole-genome sequences from Salmonella and Campylobacter isolates collected from over 800 processing facilities as part of the United States Department of Agriculture’s Food Safety Inspection Service verification sampling (2019-2025). Single-linkage clustering identified isolates sharing common origins (≤2, 4, or 8 SNPs genome-wide), which were categorized by processing complex, company, and geographical distributions to infer contamination sources. Among the isolates analyzed, 78% of Campylobacter , 77% of non-Enteritidis Salmonella , and 96% of Salmonella Enteritidis belonged to clusters spanning multiple companies and geographic regions—a pattern consistent with primary breeder origin. The geographic spread of Enteritidis isolates within clusters matched a random model, and cluster populations showed temporal turnover yet spatial synchrony—patterns explicable only by contamination from the apex of the breeding pyramid. Campylobacter showed regional clustering implying sources at lower levels of the breeding pyramid. Cluster persistence exceeded multiple production cycles (median >4 y for Campylobacter , >4.5 y for 75% of Enteritidis isolates), indicating stable contamination reservoirs upstream of processing. These results demonstrate that the primary breeders are a major source of broiler contamination and suggest that upstream interventions targeting breeding stock, in particular for Enteritidis, may represent an efficient strategy for further reducing clinical cases of foodborne illness.